ANALISIS TEORI SOME PADA PENGELOLAAN AKUN INSTRAGRAM @pesantrenbima - Yusuf, Jamaludin; Machsunah, Uun; Risnawati, Ririn; Ri'aeni, Ida (JIKE : Jurnal Ilmu Komunikasi Efek, 2022)
This study aims to find out how the implementation of Gina Luttrell's SOME (Share, Optimize, Manage, Engage) Theory in managing the @pesantrenbima instagram account in social media activities with optimal planning and strategies in order to achieve the desired goals, one of which is building maximum bond with the audience owned by social media platforms, namely utilizing the existence of Instagram as a tool (tool) in achieving its goals. This research is a qualitative descriptive study using the object of research on the Instagram account @pesantrenbima. The research subjects are admin, ustad (teacher) at Pesantren Bima, and followers. Research data obtained through observation, interviews, and documentation. The results of this study are: Share, the Instagram account @pesantrenbima is the right choice for Instagram social media and makes selection and sorting in determining the content to be presented. Optimize, the Instagram account @pesantrenbima has not used the hashtag feature provided by Instagram as a whole but the good thing that has been implemented is the presentation of content in various forms, both photos/images, videos and Instagram stories. Manage, the @pesantrenbima instagram account has properly implemented comments or direct messages from the public that will be responded to, and the Bima Pesantren social media team has carried out monitoring to evaluate the content that has been presented. Engage, the Instagram account @pesantrenbima reaches their target audience by adapting the content they post to their target audience by creating content that is interesting, up-to-date and in clear, concise, and easy-to-understand language making the information to be conveyed easily absorbed by its followers. . Keywords: Social Media, Instagram, SOME Theory